Agroecosystems in a changing climate (CRC/Taylor & Francis, 2007)
The book considers the consequences of the changes in the atmosphere and climate on the integrity, stability and productivity of agroecosystems. The book provides the theeoretical underpinning that guides scientists on what phenomena to look for beyond first order responses in the creation of sustainable agroecosystem